Civic and nationalism education for young Indonesian generation in the globalization era - Murdiono, Mukhamad; Wuryandani, Wuri (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
This study aims to describe nationalism education for young Indonesian generation in the globalization era. This is descriptive qualitative research conducted in several Senior High Schools. The data were collected through interviews, observation, and documentation. The research subjects were Civic Education teachers in Yogyakarta Province and students who attended the Civic Education classes. The collected data were then analyzed with the inductive analysis technique. The results revealed two nationalism education models for the young generation in the globalization era: promoting nationalism through Civic Education and extracurricular activities. Teachers promote nationalism by developing learning methods, learning materials, learning media, and student worksheets incorporating nationalismvalues. Meanwhile, extracurricular activities in schools were carried out through activities that promote nationalism.